CHALLENGES TO MULTILINGUALISM IN KNOWLEDGE MANAGEMENT AND SHARING: TERMINOLOGICAL CONTRIBUTIONS - da Silva, Manuel Moreira (2013)
The development of a truly multilingual information management culture, as an outcome of the development of multilingual spaces, characterized by heterogeneity and multiculturalism, as is the case of the classification systems of large international organizations, increases the need for methodologies and systems to organize information that facilitate e bring more efficiency to the proper use of these resources. In these environments, language, as the means for human communication, and terminology, as a nuclear element for the analysis, structuring and dissemination of specialized knowledge, assume an increasingly important mediation role in the communication taking place between the various interlocutors and in man-machine communication, emerging as the key link for the discovery and creation of knowledge and its effective conceptualization, representation, transmission and reuse. It is our aim, in this context, on the one hand, to analyse the role of terminology, its methodologies and resources in answering the challenges arising from the management and knowledge sharing processes that occur in multilingual environments and, on the other hand, observe the contributions of such methodologies to the processes of conceptualization and multilingual representation of domain knowledge.